Pengembangan media komik materi penjumlahan bilangan cacah kelas II SDN Randusari Yogyakarta - Egi Alridhayansah; Trisniawati Trisniawati; Mahmudah Titi Muanifah; Nelly Rhosyida; Dewi Anggreini (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study aims to (1) develop a feasible learning comic media named KOJUMCAH (Whole Number Addition Comic) for second-grade students at SDN Randusari, (2) describe the feasibility of KOJUMCAH learning media (Whole Number Addition Comic) in the second grade of SDN Randusari, and (3) describe student responses to the use of educational comic media in learning whole number addition in the second grade of SDN Randusari. This research is a Research and Development (R&D) study. The development steps used are based on Borg and Gall's development procedure theory, limited to 7 steps: potential and problems, data collection, initial product development, expert validation, design revision, limited product trial, and revision of limited product trial results. This research was conducted at SDN Randusari with a subject of 8 second-grade students (limited product trial). Data collection techniques used were observation, interviews, and questionnaires. Data analysis techniques used were qualitative and quantitative data analysis. The results of this study are as follows: (1) The development of the KOJUMCAH media, which presents a storyline-based learning of mathematics for second-grade elementary students. (2) The feasibility of the product based on validation results shows a score percentage of 80.83% from the material expert, 98.61% from the media expert, and 98.61% from the second-grade teacher, indicating that the product falls under the "very feasible" category. (3) Student responses were highly positive, with an average percentage of 88.9%, also indicating a "very feasible" category. Based on these results, it can be concluded that the KOJUMCAH (Comic on Addition of Whole Numbers) media is feasible to be used as an alternative learning media for teaching addition of whole numbers in second-grade elementary mathematics, as it meets the "very feasible" criteria based on expert validations and received highly positive responses from students.